Determinación de metales pesados en sedimentos de la desembocadura del rio Pital en época de invierno - Cabrera López, Jorge Luis (2012)
The present research carried out it at the mouth of the river Pital, in the city of Santa Rosa, during the months of March to May 2012. The objectives were: determine the levels of concentration of mercury, cadmium and lead in sediments from the mouth of the river Pital. Compare and analyze the results with the maximum permissible limits established by the Ministry of the environment for the preservation of flora and fauna. For this we take three reference points (A, B, C), where each point contained three samples, with the purpose of obtaining a greater precision in the results. Cadmium heavy metal that presented a high level of concentration in the three points of the estuary, was in an exaggerated way 108.02 mg/kg, this being of greater degree of pollution. The mercury present concentration levels higher than the maximum allowable limit, both point A and C, being the point B 0.04 mg/kg which presents contamination, however it is concluded that there is environmental contamination by mercury. The heavy metal that did not give any source of contamination was the lead being the point A, the highest concentration found 22.84 mg/kg, which does not exceed the maximum permissible limit 25 mg/kg. It is expected that high concentrations of cadmium are directly related to phosphated fertilizers, used in farms for production of banana, cacao, among others.